Peran Pendidikan Agama Kristen Terhadap Prinsip Memelihara Kesucian Dalam 1 Petrus 1:16 Di Era Disrupsi - Brian Rivan Assa; Yonatan Alex Arifianto (Jurnal Pendidikan Agama Kristen (JUPAK), 2022)
Along with the development of the era from traditional to modern, the presence of gadgets and media is increasingly diverse and growing and so massive. The amount of information scattered about garbage, fake news (hoaks), pornography, violence where no one can filter it out in any way anymore which reduces spirituality to become a challenge for believers in maintaining holiness. Using descriptive qualitative methods, it can be concluded that the role of Christian religious education on the principle of maintaining chastity in 1 Peter 1: 16 in the Era of Disruption is that Christian educators can understand the era of disruption and its challenges as part of unlimited and free information that must be watched out for. Furthermore, in the Exegesis of 1 Peter 1:16, it is found that holiness is a symbol and the essence of believers in accompanying God is prioritized. For this reason, the role of Christian Religious Education cannot be separated from building spirituality which is exemplified by spiritual leaders and believers must rely on God.